2003
DOI: 10.1080/1042819031000104079
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA 125 as a Prognostic Factor in Non-Hodgkin's Lymphoma

Abstract: Cancer antigen 125 (CA 125) is a glycoprotein expressed in normal tissues originally derived from coelomic epithelia such as peritoneum, pleura, pericardium, fallopian tubes and endometrium. Serum CA 125 levels are elevated in various benign and malignant conditions that involve stimulation of these tissues. Although elevated levels have been reported in patients with non-Hodgkin's lymphoma (NHL), its role as a prognostic factor remained uncertain. In this study, serum CA 125 levels were measured prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 22 publications
2
36
0
3
Order By: Relevance
“…However, elevated serum CA125 levels have not been observed in other reported FDC sarcomas. Although lymphoma cells do not secrete CA125, investigators have reported serum elevations of CA125 in as many as 40% of patients with non-Hodgkin's lymphoma, particularly when peritoneal, pleural or pericardial effusions were present (27). Various investigators have proposed including serum CA125 level in prognostic indices for lymphoma (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, elevated serum CA125 levels have not been observed in other reported FDC sarcomas. Although lymphoma cells do not secrete CA125, investigators have reported serum elevations of CA125 in as many as 40% of patients with non-Hodgkin's lymphoma, particularly when peritoneal, pleural or pericardial effusions were present (27). Various investigators have proposed including serum CA125 level in prognostic indices for lymphoma (28).…”
Section: Discussionmentioning
confidence: 99%
“…The other malignancies reported lower sensitivity [20,21]. It is also interesting to note that CA 125 is equally sensitive and specific for gallbladder cancer as other tumor markers like CA 19-9 and CEA in GBC [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…The positive association of gallbladder mass, weight loss, ascites, and loss of appetite with CA 125 was noted. Weight loss is also reported to be associated with increased CA 125 in Non Hodgkin Lymphomas [21]. Elevated CA 125 is closely related to cirrhotic ascites [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 40% of patients with NHL had found elevated serum CA-125 levels at diagnosis [20]. In most series CA-125 levels correlate with some features of NHL, such as stage of disease, bulky tumor, effusions, and response to therapy [20,21]. The other malignant and nonmalignant serosal fluids such as peritoneal, pleural, and pericardial effusions have been found to be associated with high serum levels of CA-125 [22].…”
Section: Discussionmentioning
confidence: 99%